2019
DOI: 10.1213/ane.0000000000003701
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated With Recovery Room Intravenous Opiate Requirement After Pediatric Outpatient Operations

Abstract: Postoperative pain requiring PACU IV opioid in children may be determined using a small set of easily obtainable perioperative variables. Our models require validation in other settings to determine their clinical usefulness.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
1
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 31 publications
0
8
1
3
Order By: Relevance
“…In the present study, girls required fewer opioids compared to boys, which contrasts with previous studies in preschool children and adolescents [ 14 , 15 ]. In a study involving pectus excavatum repair in adults, women reported higher pain intensity and greater opioid requirement after repair compared to men [ 16 ].…”
Section: Discussioncontrasting
confidence: 99%
“…In the present study, girls required fewer opioids compared to boys, which contrasts with previous studies in preschool children and adolescents [ 14 , 15 ]. In a study involving pectus excavatum repair in adults, women reported higher pain intensity and greater opioid requirement after repair compared to men [ 16 ].…”
Section: Discussioncontrasting
confidence: 99%
“…Logistic regression has also been used to create a model for prediction of PACU opioid requirements after outpatient operations in pediatric patients [34]. Similarly, Packiasabapathy et al [35] developed a predictive model to determine the association between quantitative pupillometry and opioid induced respiratory depression in children undergoing elective otolaryngological surgeries.…”
Section: Anesthetic Depth Estimation and Perioperative Opioids Requir...mentioning
confidence: 99%
“…Es importante mencionar que la mayoría de los fármacos analgésicos utilizados en niños, no siempre cuentan con los permisos de las instituciones reguladoras locales. Su uso generalmente es extrapolado de estudios realizados en población adulta y no siempre están disponibles las presentaciones más adecuadas [4], [5], [7], [11], [14], [16], [18].…”
Section: -Técnicas Farmacológicasunclassified
“…Muchas de las vías nerviosas de la transmisión y percepción del dolor se desarrollan a temprana edad, estando presentes y funcionales desde las 24 semanas de gestación intrauterina. El dolor mal tratado tiene consecuencias inmediatas y a largo plazo como empeoramiento de la calidad de vida, uso prolongado de analgésicos y aparición de dolor persistente o crónico [2], [4]. Los niños en etapa preverbal no son capaces de describir su dolor o su experiencia subjetiva y debe ser el cuidador el que aprenda a evaluarlo de manera correcta.…”
unclassified
See 1 more Smart Citation